IronFleet: Proving Safety and Liveness of Practical Distributed Systems - Hawblitzel, Chris; Howell, Jon; Kapritsos, Manos; Lorch, Jay; Parno, Bryan; Stephenson, Justine; Setty, Srinath; Zill, Brian (Communications of the ACM, 2017)
Distributed systems are notorious for harboring subtle bugs. Verification can, in principle, eliminate these bugs, but it has historically been difficult to apply at full-program scale, much less distributed system scale. We describe a methodology for building practical and provably correct distributed systems based on a unique blend of temporal logic of actions-style state-machine refinement and Hoare-logic verification. We demonstrate the methodology on a complex implementation of a Paxos-based replicated state machine library and a lease-based sharded key-value store. We prove that each obeys a concise safety specification as well as desirable liveness requirements. Each implementation achieves performance competitive with a reference system. With our methodology and lessons learned, we aim to raise the standard for distributed systems from "tested" to "correct."